2011
DOI: 10.1121/1.3613939
|View full text |Cite
|
Sign up to set email alerts
|

Generalized response of a sphere embedded in a viscoelastic medium excited by an ultrasonic radiation force

Abstract: The response of an embedded sphere in a viscoelastic medium excited by acoustic radiation force has been studied in both the time-and frequency-domains. This model is important because it can be used to characterize the viscoelastic properties of the medium by fitting the response to the theoretical model. The Kelvin-Voigt model has been used exclusively in these models. An extension to the previously reported models is described so that any viscoelastic rheological model can be used. This theoretical developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 22 publications
4
31
0
1
Order By: Relevance
“…In order to preserve the obtained mesoscopic structure after insonification, it has been proposed to work in photocurable resins [18] or in yield-stress fluids [19]. However, while the acoustic radiation force is well characterized in simple inviscid fluids, the effect of viscosity on F rad is still under debate [20][21][22][23][24][25] and only a few studies have been devoted to the general case of viscoelastic media [26][27][28][29][30]. It is thus of growing interest to characterize the acoustic radiation force in complex, soft materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to preserve the obtained mesoscopic structure after insonification, it has been proposed to work in photocurable resins [18] or in yield-stress fluids [19]. However, while the acoustic radiation force is well characterized in simple inviscid fluids, the effect of viscosity on F rad is still under debate [20][21][22][23][24][25] and only a few studies have been devoted to the general case of viscoelastic media [26][27][28][29][30]. It is thus of growing interest to characterize the acoustic radiation force in complex, soft materials.…”
mentioning
confidence: 99%
“…Here, we propose a different approach: assuming that the rheology of the gel is known, we measure the acoustic radiation force through the steady-state displacement δr max of a spherical intruder exposed to much longer insonification. Indeed, assuming a no-slip boundary condition at the sphere surface, F rad is related to δr max by [27,29] F rad = 6πG 0 aδr max ,…”
mentioning
confidence: 99%
“…In this study, SWE measurements were limited to 400 Hz due to shear wave attenuation and low signal-tonoise ratio. The KVFD storage, G s (ω), and loss, G l (ω), modulus are described by [19]:…”
Section: Methodsmentioning
confidence: 99%
“…In incompressible medium Young’s modulus E j , is three times its shear modulus, μ1j, i.e., Ej=3μ1j for each layer. It has been demonstrated that this model adequately describes tissue and tissue-mimicking phantom behavior under short acoustic radiation force (Aglyamov et al, 2007, Urban and Nenadic, 2011, Yoon et al, 2012, Yoon et al, 2013, Yoon et al, 2011). We assume that shear stress applied on the tissue surface is zero, i.e.…”
Section: Methodsmentioning
confidence: 99%